Berrios' insulting remark - Maldonado, A. W. (My University, 1991)
Beerios' insulting remark, The San Juan Star
Keywords: Berrios Martínez, Rubén; Hernández Colón, Rafael; Romero Carceló, Carlos; Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.